A Meta-Analysis on the Association Between TNFSF4 Polymorphisms (rs3861950 T > C and rs1234313 A > G) and Susceptibility to Coronary Artery Disease - Liu, Shuyan; Wang, Xiju; Yu, Shoujun; Yan, Miao; Peng, Yue; Zhang, Guilong; Xu, Zhaowei (Frontiers in Physiology, 2020)
Background: Coronary artery disease (CAD) remains the leading cause of mortality worldwide, and its susceptibility is closely associated with the genetic modifications. The association between inflammation and CAD has been investigated indetail. This meta-analysis was conducted based on the PRISMA guidelines to evaluate the association between the tumor necrosis factor superfamily member 4 (TNFSF4) gene polymorphisms (rs3861950 T > C and rs1234313 A > G) and the risk of CAD. Methods：The selected criteria included 11 eligible articles containing 18 studies (9 studies included 7395 cases and 5296 controls for rs3861950 and 9 studies with 6951 cases and 4959 controls for rs1234313). Correlations between the two polymorphisms and CAD were estimated by pooling the odds ratios (ORs) with 95% confidence interval (95% CI) in allelic, dominant, recessive, heterozygous, and homozygous models. Results: The pooled analyses demonstrated that the rs3861950 T > C polymorphism was significantly associated with an increased risk of CAD in the Asian population in the allelic model, dominant model, and homozygous model. Furthermore, subgroup analysis based on disease type showed that TNFSF4 rs3861950 T > C had a robust correlation with increased risk of cerebral infarction (CI) in the allelic model, dominant model, heterozygous model, and homozygous model. However, the rs1234313 A > G polymorphism mostly tended to decrease the risk of CAD in the Asian and Caucasian populations in the allelic and dominant model. This single nucleotide polymorphism (SNP) had a close relation to myocardial infarction (MI) susceptibility in the allelic model, dominant model, and heterozygous model. Conclusion: This meta-analysis identified two novel SNPs in TNFSF4 significantly associated with CAD susceptibility.